Catalytic Spectrophotometric Method for Determination of Formaldehyde Based on its Catalytic Effect on the ReactionBetween Bromate and Safranin - Mohsen Keyvanfard (E-Journal of Chemistry)
The reaction monitored spectrophotometrically by measuring the decrease in absorbance of the reaction mixture at 533 nm. The fixed-time method was used for the first 60s. For initiation of the reaction, under the optimum conditions, in the concentration range of 0.02-1.5 μg mL–1 formaldehyde can be determined with a limit of detection 9.5 ng mL–1. The relative standard deviation of five replicate measurements is 2.3% for 0.5 μg mL–1 of formaldehyde. The method was used for the determination of formaldehyde in water samples with satisfactory results. A new simple and fast catalytic kinetic method for the determination of trace amount of formaldehyde is described. The method is based on the catalytic effect of formaldehyde on the oxidation of safranin by bromate in the present of sulfuric acid.